The B.S.E.E. internship program of the Cagayan Teachers College practices and problems - De los Santos, Concepcion (Petralba) 1936- (s.n.], 1971)
The practices and problems relative to the BSEE internship program of the Cagayan Teachers College were determined. To gather data, the descriptive survey method was used using documentary analysis, observation, interview, and questionnaire as tools.